FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN KONSUMEN E-COMMERCE MENGGUNAKAN DIGITAL ACCUMULATED BALANCE PAYMENT SYSTEM (PAY LATER) - Jaya*, Rama Chandra; Triono, Sunu Puguh Hayu (JURISMA : Jurnal Riset Bisnis & Manajemen, 2022)
This study contains of description and influence of the factors that influence consumer decision to use the Accumulated Balance Payment System (Pay later). This research uses descriptive and quantitative methods with analysis using Structural Equation Modeling and SmartPLS. The results of the hypothesis test showed that the variables Demographics, Orientations, and Psychographics have a positive and significant effect on the Consumer Consumer Payment Technology Use Decision. Based on the results the role of the closest family such as parents, husband, or wife in granting permission to use Pay later is very important. Companies need to implement the Familly Sharing Payment System in a consumer Pay later account. This is expected to provide ease of payment and get more users, provide solutions for family members who have not worked, and provide balanced restrictions and ease of payments that are integrated into one main account. Keywords: Pay later, Payment Technology, Accumulated Balance, Sharing Payment, Consumer Decision